Evidence of Infection of Human Embryonic Stem Cells by SARS-CoV-2 - Zeng, Weijie; Xing, Fan; Ji, Yanxi; Yang, Sidi; Xu, Tiefeng; Huang, Siyao; Li, Chunmei; Wu, Junyu; Cao, Liu; Guo, Deyin (Frontiers in Cellular and Infection Microbiology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was initially described to target the respiratory system and now has been reported to infect a variety of cell types, including cardiomyocytes, neurons, hepatocytes, and gut enterocytes. However, it remains unclear whether the virus can directly infect human embryonic stem cells (hESCs) or early embryos. Herein, we sought to investigate this question in a cell-culture system of hESCs. Both the RNA and S protein of SARS-CoV-2 were detected in the infected hESCs and the formation of syncytium was observed. The increased level of subgenomic viral RNA and the presence of dsRNA indicate active replication of SARS-CoV-2 in hESCs. The increase of viral titers in the supernatants revealed virion release, further indicating the successful life cycle of SARS-CoV-2 in hESCs. Remarkably, immunofluorescence microscopy showed that only a small portion of hESCs were infected, which may reflect low expression of SARS-CoV-2 receptors. By setting |log2 (fold change)| > 0.5 as the threshold, a total of 1,566 genes were differentially expressed in SARS-CoV-2-infected hESCs, among which 17 interferon-stimulated genes (ISGs) were significantly upregulated. Altogether, our results provide novel evidence to support the ability of SARS-CoV-2 to infect and replicate in hESCs.